Pillow plate heat exchanger weld shape optimization using approximation and parallel parameterized CFD and non-uniform rational B-splines. (February 2020) - Eldeeb, Radia; Aute, Vikrant; Radermacher, Reinhard
Abstract: Plate heat exchangers (PHXs) are compact with small approach temperature, and desirable thermal-hydraulic characteristics. It is greatly desirable to create novel PHX designs that utilize less material and less volume while attaining similar heat transfer performance and thus contribute significantly to energy conservation while lowering the environmental impact as well. Pillow Plate Heat Exchanger (PPHX) is a type of PHX with a complex wavy structure with desirable thermal-hydraulic characteristics, but yet an economical manufacturing process especially when compared to corrugated Chevron PHX (CPHX) which requires a special die for each design. PPHX has great design flexibility allowing novel designs to be created in a simpler and less costly process which provides them with a good potential to outperform other types of PHXs. PPHXs are more commonly used in chemical and process industry with limited research in Heating, Ventilating, Air Conditioning, and Refrigeration (HVAC&R) applications. In this study, the optimization of PPHXs in order to maximize their thermal-hydraulic performance, including weld shape optimization using novel weld shapes created using Non-Uniform Rational B-Splines (NURBS), is studied. Sensitivity analysis is conducted on the optimal designs to provide insights into factors affecting their performance. The potential enhancement is up to 36% improvement in heat transfer coefficient and 67% reduction in pressure drop as compared to a selected PPHX baseline design with circular spot welds. The optimal designs are compared to optimal CPHX designs from literature showing a potential improvement of 38% for heat transfer coefficient, and a reduction of 72% in pressure drop.